2022
DOI: 10.1590/0102-33062020abb0500
|View full text |Cite
|
Sign up to set email alerts
|

Quilombola Ethnomedicine: The Role of Age, Gender, and Culture Change

Abstract: Non-indigenous communities are particularly insightful in terms of understanding the process of healing plant acquisition and loss. This study explores the traditional medicinal plant knowledge and use of a long-isolated, Africandescended community in the Atlantic rainforests of northeastern Brazil. We investigated the primary plant species used and their therapeutic applications. We hypothesized that women and the oldest members of the community would be the most knowledgeable about medicinal plants. We carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
4
0
2
Order By: Relevance
“…Essa preferência pode ser justificada pela concentração dos princípios ativos necessários para o tratamento, facilidade de acesso, disponibilidade ao longo do ano e tradição nas comunidades quilombolas (Oliveira et al, 2022;Santana, Voeks, Funch, 2022).…”
Section: Resultsunclassified
“…Essa preferência pode ser justificada pela concentração dos princípios ativos necessários para o tratamento, facilidade de acesso, disponibilidade ao longo do ano e tradição nas comunidades quilombolas (Oliveira et al, 2022;Santana, Voeks, Funch, 2022).…”
Section: Resultsunclassified
“…In certain regions, females are closer to the identification and medicinal uses of local flora than males (Tuler and da Silva 2014;Acosta-Naranjo et al 2021;Teixidor-Toneu et al 2021). In other regions, there are no significant gender differences in plant knowledge (de Santana et al 2022). A study in a Caribbean horticultural village reported that males acquired a stronger grasp of tree-related knowledge, while females excelled in learning about medicinal plants (Quinlan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Both men and women can demonstrate the same knowledge within a medical system, depending on the sociocultural context in which the community is located. Santana et al (2022) noticed this trend, where men living in Salamina show a level of medicinal plant knowledge equivalent to women regarding self-care practices. Kidane et al (2018) and Lautenschläger et al (2018) also found that gender did not have a significant impact on the traditional use of medicinal plants in their study communities.…”
Section: Does Gender Influence the Richness Of Medicinal Species?mentioning
confidence: 90%
“…For instance, Matejić et al (2020) observed distinct preferences in the use of medicinal plants between men and women in Svrljig and Tiok for treating different diseases in each group; the study by Díaz-Reviriego et al (2016) showed that only women reported species that can be used in reproductive health, such as fertility, contraception, among others, as well as childhood illnesses. In Salamina, Santana et al (2022) found that women have a more diversified repertoire of medicinal plants, especially for spiritual protection, indicating that health preservation encompasses both the physical and spiritual aspects. In turn, Alqethami et al (2020) observed that women exhibit a higher frequency of citations of uses and species related to reproductive diseases.…”
Section: Does Gender Influence the Composition Of Known And Used Medi...mentioning
confidence: 99%